The legal culture of the European Court of Human Rights - Arold Lorenz, Nina-Louisa (Martinus Nijhoff Publishers, 2007)
Without understanding the legal culture of the judges a full understanding of Strasbourg's rulings seems hardly possible. Through interviews, field observations and case law analysis, this book aims to fill this need and offers a fresh approach towards convergence in Europe.
Keywords: European Court of Human Rights.; European Court of Human Rights; Human rights -- Europe.; Judges -- Europe.; Judicial opinions -- Europe.; Justice, Administration of -- Europe.; Court administration -- Europe.; Droits de l'homme (Droit international) -- Europe.; Jugements -- Europe.; Tribunaux -- Administration -- Europe.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; Court administration; Human rights; Judges; Judicial opinions; Justice, Administration of; Europe